Nilai-Nilai Pancasila dalam Pembaruan Hukum Adat Tantangan dan Peluang dalam Era Globalisasi - Ashfiya Nur Atqiya; Ahmad Muhamad Mustain Nasoha; Nabella Indah Rismawati; Dewi Rahmawati Yundha Saputri; Arfian Nisa Urrofi'ah (Pemuliaan Keadilan, 2024)
Customary law reform in Indonesia in the context of globalization raises significant challenges and opportunities. The values of Pancasila, as the ideological foundation of the nation, play an important role in ensuring that customary law reform remains relevant, fair and rooted in local culture. Globalization encourages the modernization and homogenization of the legal system, which often contradicts the principles of customary law based on local wisdom. This article examines how Pancasila values, such as humanity, social justice, unity, and deliberation, can be integrated in the process of customary law reform to remain relevant amid global dynamics. This research uses a qualitative approach with the methods of literature study, interviews, and document analysis. Literature study was conducted to understand the theoretical context of customary law reform and Pancasila values, while interviews were conducted with legal experts, academics, and traditional leaders to obtain empirical perspectives on challenges and opportunities in customary law reform. Document analysis was conducted on policies and regulations relating to customary law and the implementation of Pancasila values in Indonesia. The results show that customary law reform based on Pancasila has great potential to deliver a legal system that is more inclusive and responsive to the needs of local communities. Key challenges identified include difficulties in harmonizing customary law with national and international law and homogenizing pressures from global standards. However, opportunities are also found in the ability of updated customary law to provide more culturally and locally relevant dispute resolution alternatives. The integration of Pancasila values is believed to strengthen the position of customary law within national and global legal frameworks.ract